A numerical simulation of a strong wind event in January 2013 at King Sejong station, Antarctica. (11th March 2019) - Kwon, Hataek; Park, Sang‐Jong; Lee, Solji; Kim, Baek‐Min; Choi, Taejin; Kim, Seong‐Joong
Abstract : A strong wind event (SWE), so‐called "severe gale", with a 10 min average wind speed of above 22 m/s occurred on 7 January 2013 at the King Sejong station (KSJ) on the tip of the Antarctic Peninsula (AP). We examine the cause of the SWE and assess the short‐term predictability of such an event, using the state‐of‐the‐art Polar Weather Research and Forecasting (Polar WRF) model. The simulation results, initialized at 0000 UTC 6 January 2013, the day prior to the occurrence of the SWE, produce the most accurate representation of the SWE in terms of strength (∼94% of the peak wind speed). Both model results and observational records reveal that the SWE is mainly caused by the approach of a deep depression with the central pressure of 950 hPa. On top of this synoptic configuration, a particular shape of topography of the AP plays a non‐negligible role for further intensification of the wind at KSJ. As the cyclone approaches the AP, the sea‐level pressure becomes lower and is deformed around the AP due to the topography, driving southeasterly winds traversing the AP. The continuous flow overriding the AP generates a downslope windstorm at the lee side of the AP. The windstorm effect driven by the deformation of sea‐level pressure by the topography of the AP is not properly represented in the coarser‐resolution (27 km) model domain compared with higher (3 and 9 km) resolutions. We conclude that the SWE at KSJ on 7 January 2013 is caused by the combined effect of a synoptic‐scale low‐pressure system with local topography of the AP. Abstract : It is the model domain for different horizontal resolutions and the Fig.1 b is the enlarged part of d03.